Solid heat medium
Patent Information
- Application Number
- JP2023140908
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明者らは、相転移材料の粉体を固化させた固体熱媒体に圧力を印加して得られる放熱量と、当該固体熱媒体から圧力を解放して得られる吸熱量とを良好に確保すべく、鋭意研究を行った。そして、研究の結果、本発明者らは、固体熱媒体に圧力が印加されたときに相転移材料の粉体の一部に圧力が伝達されていないおそれがあることや、固体熱媒体から圧力が解放されたときに相転移材料の粉体の一部が加圧される前の状態にスムースに戻っていない(固体熱媒体の一部が膨張または収縮していない)おそれがあることを見出した。これらの知見を踏まえ、本開示の固体熱媒体には、少なくとも基油成分および増ちょう成分が配合されたグリスが添加される。これにより、グリスの基油成分の潤滑作用により圧力の印加時および解放時における相転移材料の粉体の流動性を良好に確保すると共に、固体熱媒体への圧力の印加および解放が繰り返されてもグリスの増ちょう成分の作用により固体熱媒体を固体状態(圧粉状態)維持することができる。この結果、固体熱媒体に圧力が印加されるときに相転移材料の粉体同士間の空隙を減少させることが可能になり、相転移材料の粉体の全体を概ね均等に加圧して、固体熱媒体に圧力を印加して得られる放熱量を良好に確保することができる。更に、固体熱媒体から圧力が解放されるときには、グリスの潤滑作用により相転移材料の粉体の全体を加圧される前の状態にスムースに戻す(膨張または縮小させる)ことが可能になるので、固体熱媒体から圧力を解放して得られる吸熱量を良好に確保することができる。加えて、固体熱媒体にグリスを添加することで、固体熱媒体と、当該固体熱媒体に圧力を印加する加圧部材との固着を抑制することも可能になる。
Smart Images

Figure 2025034501000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to solid heat transfer media that undergo a phase transition between high and low temperature phases in response to the application and release of pressure. [Background technology]
[0002] Rubidium-manganese-iron cyanide complex (Rb x Mn[Fe(CN)6] y ) is known (see, for example, Patent Document 1). The rubidium-manganese-iron cyano complex exhibits bistability in two states: a high-temperature phase in which the valences of manganese and iron are Mn(II)-Fe(III), and a low-temperature phase in which the valences of manganese and iron are Mn(III)-Fe(II). When pressure is applied to a heat medium containing such a rubidium-manganese-iron cyano complex, the phase transition temperature from the high-temperature phase to the low-temperature phase and the phase transition temperature from the low-temperature phase to the high-temperature phase increase. That is, when pressure is applied to the heat medium, the phase transition temperature from the high-temperature phase to the low-temperature phase, which is lower than the phase transition temperature from the low-temperature phase to the high-temperature phase, increases, so that the rubidium-manganese-iron cyano complex can be caused to undergo a phase transition from the high-temperature phase to the low-temperature phase and heat can be released from the heat medium without significantly lowering the temperature of the heat medium. In addition, when the pressure applied to the heat medium containing the rubidium-manganese-iron cyano complex is released, the phase transition temperature from the high-temperature phase to the low-temperature phase and the phase transition temperature from the low-temperature phase to the high-temperature phase decrease. Therefore, by releasing the pressure applied to the heat medium, it is possible to cause the rubidium-manganese-iron cyano complex to undergo a phase transition from a low-temperature phase to a high-temperature phase, and to have the heat medium absorb heat, without significantly increasing the temperature of the heat medium. By repeatedly applying and releasing pressure to the heat medium, heat can be transferred from a low-temperature part to a high-temperature part via the heat medium. Furthermore, Patent Document 1 discloses a heat absorption and release system including a solid heat medium obtained by solidifying powder of rubidium-manganese-iron cyano complex, and a pressurizing device for pressurizing the solid heat medium. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2023 / 002698 Summary of the Invention [Problem to be solved by the invention]
[0004] However, even if a solid heat medium containing a phase change material as described in Patent Document 1 is subjected to a phase change by applying pressure and then releasing the pressure, it is difficult to obtain the theoretically expected amount of heat dissipation (amount of temperature increase of the solid heat medium) or amount of heat absorption (amount of temperature decrease of the solid heat medium).
[0005] Therefore, a main objective of the present disclosure is to satisfactorily ensure the amount of heat dissipation obtained by applying pressure to a solid heat medium containing a phase change material, and the amount of heat absorption obtained by releasing pressure from the solid heat medium. [Means for solving the problem]
[0006] The solid heat transfer medium disclosed herein is a solid heat transfer medium obtained by solidifying powder of a phase change material that undergoes a phase change from a high-temperature phase to a low-temperature phase in response to the application of pressure and that undergoes a phase change from the low-temperature phase to the high-temperature phase in response to the release of pressure, and contains, as an additive, grease blended with at least a base oil component and a thickening component.
[0007] The present inventors have conducted intensive research in order to ensure a good heat dissipation amount obtained by applying pressure to a solid heat medium obtained by solidifying powder of a phase-change material, and a good heat absorption amount obtained by releasing pressure from the solid heat medium. As a result of the research, the present inventors have found that when pressure is applied to the solid heat medium, pressure may not be transmitted to a part of the powder of the phase-change material, and when pressure is released from the solid heat medium, a part of the powder of the phase-change material may not smoothly return to the state before pressure was applied (a part of the solid heat medium may not expand or contract). Based on these findings, a grease containing at least a base oil component and a thickening component is added to the solid heat medium of the present disclosure. As a result, the lubricating action of the base oil component of the grease ensures good fluidity of the powder of the phase-change material when pressure is applied and released, and the action of the thickening component of the grease allows the solid heat medium to be maintained in a solid state (compressed powder state) even if pressure is repeatedly applied and released to the solid heat medium. As a result, when pressure is applied to the solid heat medium, it is possible to reduce the gaps between the powder particles of the phase-change material, and the entire powder particles of the phase-change material are generally evenly pressurized, so that the amount of heat dissipation obtained by applying pressure to the solid heat medium can be secured satisfactorily. Furthermore, when pressure is released from the solid heat medium, the lubricating effect of the grease allows the entire powder particles of the phase-change material to smoothly return (expand or shrink) to the state before pressure was applied, so that the amount of heat absorption obtained by releasing pressure from the solid heat medium can be secured satisfactorily. In addition, by adding grease to the solid heat medium, it is also possible to suppress adhesion between the solid heat medium and the pressurizing member that applies pressure to the solid heat medium. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view showing a heat absorption and dissipation system including a solid heat medium according to the present disclosure. [Diagram 2] FIG. 1 is a cross-sectional view showing a heat absorption and dissipation system including a solid heat medium according to the present disclosure. [Diagram 3] 1 is a table showing the evaluation results of the amount of heat released obtained by applying pressure to a solid heat transfer medium of a comparative example not containing an additive. [Figure 4]1 is a table showing the evaluation results of the amount of heat absorption obtained by releasing pressure from a solid heat transfer medium of a comparative example not containing an additive. [Diagram 5] 1 is a table showing the evaluation results of the amount of heat dissipation obtained by applying pressure to the solid heat transfer medium of the present disclosure. [Figure 6] 1 is a chart showing the evaluation results of the amount of heat absorption obtained by releasing pressure from the solid heat transfer medium of the present disclosure. [Figure 7] 13 is a table showing the evaluation results of the amount of heat released obtained by applying pressure to another solid heat transfer medium of the present disclosure. [Figure 8] 13 is a chart showing the evaluation results of the amount of heat absorption obtained by releasing pressure from another solid heat transfer medium of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Next, an embodiment of the present disclosure will be described with reference to the drawings.
[0010] FIG. 1 is a schematic diagram showing a heat absorption and dissipation system 1 including a solid heat medium 5 according to the present disclosure. The heat absorption and dissipation system 1 shown in the figure includes, in addition to the solid heat medium 5, a container 2, a receiving member 3, and a pressure member 4. The container 2 is formed into a cylindrical shape from a heat insulating material. The receiving member 3 is formed into a disk shape, and is fixed inside the lower end of the container 2 to form the bottom of the container 2. The pressure member 4 is supported by the inner peripheral surface of the container 2 so as to be slidable in the axial direction of the container 2, and is moved in the axial direction of the container 2 by a driving device (not shown). The solid heat medium 5 is a rubidium-manganese-iron cyano complex (Rb x Mn[Fe(CN)6] y (hereinafter referred to as "RbMnFe complex"), which is an insoluble powder of RbMnFe complex, is solidified to form a generally cylindrical shape having an outer diameter smaller than the inner diameter of the container 2. The solid heat transfer medium 5 is placed inside the container 2 such that its outer peripheral surface does not contact the inner peripheral surface of the container 2, and its lower end surface in the figure contacts the upper surface (bottom surface) of the receiving member 3 in the figure. The pressurizing member 4 is placed inside the container 2 such that its lower surface in the figure contacts the upper end surface in the figure of the solid heat transfer medium 5.
[0011] The RbMnFe complex is a charge-transfer phase transition complex that has a network structure in which iron and manganese are three-dimensionally cross-linked by cyano groups, and has a crystal structure in which rubidium ions are arranged alternately in the voids of the framework. Such RbMnFe complexes exhibit bistability in two states: a high-temperature phase in which the valences of manganese and iron are Mn(II)-Fe(III), and a low-temperature phase in which the valences of manganese and iron are Mn(III)-Fe(II). In other words, the RbMnFe complex has a first phase transition temperature T LH When heated to above the first phase transition temperature T LH The second phase transition temperature T HL Below this temperature, a phase transition occurs from the high-temperature phase to the low-temperature phase, releasing heat.
[0012] In addition, the phase transition of the RbMnFe complex is accompanied by thermal hysteresis, and after the RbMnFe complex undergoes a phase transition from the low-temperature phase to the high-temperature phase, it stores the heat absorbed during the phase transition to the high-temperature phase until it transitions back to the low-temperature phase. Furthermore, by changing the ratio of rubidium to manganese in the RbMnFe complex, the two phase transition temperatures T LH ,T HL and the phase transition temperature T LH and the phase transition temperature T HL In the RbMnFe complex forming the solid heat transfer medium 5, the ratio x of rubidium to manganese is set to 0.94≦x≦1. This changes the phase transition temperature T LH and the phase transition temperature T HL and the phase transition temperature T LH ,T HL The rate of change of magnetic susceptibility (gradient of change) in the vicinity can be made larger.
[0013] Furthermore, when the RbMnFe complex is pressurized, the phase transition temperature from the high-temperature phase to the low-temperature phase, T HL and the phase transition temperature T from the low-temperature phase to the high-temperature phase LH Basically, the higher the pressure applied to the RbMnFe complex, the higher the phase transition temperatures T HL ,TLH Therefore, as shown in FIG. 2, if the pressure member 4 is moved toward the receiving member 3 by a driving device (not shown) to apply pressure to the solid heat transfer medium 5, the phase transition temperature T LH The phase transition temperature T from the high-temperature phase to the low-temperature phase is lower than HL Since the temperature of the solid heat medium 5 becomes high, it is possible to cause the RbMnFe complex to undergo a phase transition from a high-temperature phase to a low-temperature phase without significantly lowering the temperature of the solid heat medium 5. As a result, in the heat absorption and dissipation system 1, by applying pressure to the solid heat medium 5 by the pressurizing member 4, heat is released from the solid heat medium 5 to a heating target (not shown) in response to the phase transition of the RbMnFe complex from the high-temperature phase to the low-temperature phase, and the heating target can be heated. When pressure is applied to the solid heat medium 5, the solid heat medium 5 contracts in the axial direction and expands in the radial direction so that its outer circumferential surface comes into contact with the inner circumferential surface of the container 2, as shown in FIG. 2.
[0014] In contrast, when the pressure applied to the RbMnFe complex is released, the phase transition temperature from the high-temperature phase to the low-temperature phase, T HL and the phase transition temperature T from the low-temperature phase to the high-temperature phase LH decreases (returns to original state). Therefore, by releasing the pressure applied to the solid heat medium 5 (reducing the applied pressure to zero), it becomes possible to cause the RbMnFe complex to undergo a phase transition from a low-temperature phase to a high-temperature phase without significantly increasing the temperature of the solid heat medium 5. As a result, in the heat absorption and dissipation system 1, by releasing the pressure applied to the solid heat medium 5 (see FIG. 1), the solid heat medium 5 can absorb heat from a cooling target (not shown) in response to the phase transition of the RbMnFe complex from the low-temperature phase to the high-temperature phase, thereby cooling the cooling target. When the pressure is released from the solid heat medium 5, the solid heat medium 5 expands in the axial direction and contracts in the radial direction so that the outer circumferential surface is separated from the inner circumferential surface of the container 2.
[0015] In addition, by doping the Fe in the RbMnFe complex with trivalent cobalt ions, more specifically, hexacyanocobalt ions, the phase transition temperature T LHFor example, if the amount of cobalt doped in the RbMnFe complex is 0 to 7%, the phase transition temperature T HL is set to a value in the range of 248K to 307K, and if it is 2 to 7%, the phase transition temperature T HL can be set to a value within the range of 248 K to 290 K. Furthermore, by doping the Mn (manganese) of the RbMnFe complex with divalent copper (Cu) ions, divalent nickel (Ni) ions, or divalent zinc (Zn) ions, the phase transition temperature T LH More specifically, the doping amount of divalent copper (Cu) ions relative to Mn in the RbMnFe complex is set to, for example, 6 to 8%, or the doping amount of divalent nickel (Ni) ions or divalent zinc (Zn) ions is set to, for example, 2 to 8%, thereby lowering the phase transition temperature T HL can be set to a value within a range of 250 K to 290 K. In addition, even if the Mn in the RbMnFe complex is doped with divalent iron (Fe) ions, if the doping amount is kept low (for example, 4% or less), the phase transition temperature T LH can be reduced.
[0016] On the other hand, when the Mn (manganese) of the RbMnFe complex is doped with divalent cobalt (Co) ions, the phase transition temperature T LH This makes it possible to realize a heat absorption / dissipation system that operates in a high-temperature environment by using divalent cobalt ions as a dopant for the RbMnFe complex. In addition, when zinc is used as a dopant for the RbMnFe complex, the phase transition temperature T LH and the phase transition temperature T HL By setting the doping amount to 4-8%, it is possible to reduce the difference (hysteresis width) between the phase transition temperature T LH and the phase transition temperature T HL The difference (hysteresis width) between the phase transition temperature T LHand the phase transition temperature T HL Therefore, an increase in the difference (hysteresis width) between the measured value and the actual value can be effectively suppressed.
[0017] Here, even if a conventional solid heat medium containing the above-mentioned RbMnFe complex undergoes a phase transition by applying pressure or releasing pressure, it is difficult to obtain the theoretically expected heat release amount (temperature rise amount of the solid heat medium) or heat absorption amount (temperature drop amount of the solid heat medium). For this reason, the present inventors have conducted intensive research in order to satisfactorily secure the heat release amount obtained by applying pressure to a solid heat medium obtained by solidifying powder of the RbMnFe complex and the heat absorption amount obtained by releasing pressure from the solid heat medium. In the research, the present inventors evaluated the heat release amount obtained by applying pressure to a comparative solid heat medium that does not contain an additive, and the heat absorption amount obtained by releasing pressure from the comparative solid heat medium that does not contain an additive. The comparative solid heat medium is a RbMnFe complex doped with 9% divalent zinc (Zn) ions relative to Mn (manganese) and solidified into a roughly cylindrical shape by pressurizing it inside a mold without adding any additive.
[0018] FIG. 3 shows the evaluation results of the amount of heat dissipation obtained by applying pressure to a comparative solid heat medium containing no additive. FIG. 3 shows the temperature change at the center (the center of the central cross section in the axial direction) of the solid heat medium when a pressure of 500 MPa is applied to the comparative solid heat medium for a predetermined time (for example, about 30 seconds) by a test device having a configuration similar to that of the heat absorption and dissipation system 1 in an environment where the room temperature is about 20°C. The maximum temperature rise when a pressure of 500 MPa is applied to the comparative solid heat medium was 18°C. Therefore, even if the comparative solid heat medium is applied to the heat absorption and dissipation system 1, it is difficult to heat the heating target well.
[0019] FIG. 4 shows the evaluation results of the amount of heat absorption obtained by applying pressure to a comparative solid heat medium containing no additive and then releasing the pressure from the solid heat medium. FIG. 4 shows the temperature change at the center of the solid heat medium (the center of the central cross section in the axial direction) when a pressure of 500 MPa is applied to the comparative solid heat medium for a predetermined time by the above-mentioned test device in an environment where the room temperature is about 20°C, and then the pressure is released from the solid heat medium. The maximum temperature drop when a pressure of 500 MPa is applied to the comparative solid heat medium and then the pressure is released is 12°C. Therefore, even if the comparative solid heat medium is applied to the heat absorption and release system 1, it is difficult to cool the cooling target well.
[0020] After obtaining the evaluation results of Figures 3 and 4, the inventors further analyzed and considered the cause of the insufficient amount of heat released from and the insufficient amount of heat absorbed by the solid heat medium containing no additives. As a result, the inventors found that when pressure is applied to the solid heat medium, the pressure may not be transmitted to a part of the powder of the RbMnFe complex, and when pressure is released from the solid heat medium, a part of the powder of the RbMnFe complex may not smoothly return to the state before pressure was applied (a part of the solid heat medium may not expand or contract).
[0021] Based on these findings, the inventors decided to add grease and resin powder containing at least a base oil component and a thickening component to the solid heat medium 5 formed of the RbMnFe complex. In this embodiment, the grease is a silicon-based grease containing silicon oil as a base oil and silica powder as a thickening agent. In addition, in this embodiment, the resin powder is polypropylene powder with an average particle size of about 5 μm. The solid heat medium 5 is formed into a substantially cylindrical shape by pressing and solidifying a mixture of RbMnFe complex powder doped with 9% divalent zinc (Zn) ions relative to Mn (manganese), grease, and resin powder inside a mold. The amount of grease added to the solid heat medium 5 is 6% by weight, and the amount of resin powder added to the solid heat medium 5 is 10% by weight. The grease and resin powder, which are additives, also function as binders for solidifying the RbMnFe complex powder.
[0022] FIG. 5 shows the evaluation results of the amount of heat dissipation obtained by applying pressure to the solid heat medium 5 to which grease and resin powder have been added. FIG. 5 shows the temperature change at the center of the solid heat medium 5 (the center of the central cross section in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5 for a predetermined time (for example, about 30 seconds) by the above-mentioned test device in an environment where the room temperature is about 20°C. The maximum temperature rise when a pressure of 500 MPa is applied to the solid heat medium 5 was 46°C. It can be seen from these evaluation results that if the solid heat medium 5 is applied to the heat absorption and dissipation system 1, the heating target can be heated well.
[0023] That is, in the solid heat medium 5, the lubricating action of the base oil component of the grease ensures good fluidity at the micro level of the powder of the RbMnFe complex when pressure is applied and released, and the action of the thickening component of the grease makes it possible to maintain the solid state (compressed powder state) of the solid heat medium 5 even if pressure is repeatedly applied and released. Furthermore, the solid heat medium 5 contains resin powder (polypropylene powder) in addition to the grease, and the gaps between the powder particles of the RbMnFe complex can be filled with the resin powder. As a result, it is possible to significantly reduce the gaps between the powder particles of the RbMnFe complex when pressure is applied to the solid heat medium 5, and the entire powder of the RbMnFe complex can be pressurized almost evenly, thereby ensuring a good amount of heat dissipation obtained by applying pressure to the solid heat medium 5. In addition, by adding grease to the solid heat medium 5, it is also possible to suppress adhesion between the solid heat medium 5 and the pressurizing member 4 that applies pressure to the solid heat medium 5.
[0024] FIG. 6 shows the evaluation results of the amount of heat absorption obtained by applying pressure to the solid heat medium 5 to which grease and resin powder have been added, and then releasing the pressure from the solid heat medium 5. FIG. 6 shows the temperature change at the center of the solid heat medium 5 (the center of the cross section at the center in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5 for a predetermined time by the above-mentioned test device in an environment where the room temperature is about 20°C, and then the pressure is released from the solid heat medium 5. The maximum temperature drop when a pressure of 500 MPa is applied to the solid heat medium 5 and then the pressure is released is 34°C. From these evaluation results, it can be understood that if the solid heat medium 5 is applied to the heat absorption and dissipation system 1, the cooling target can be cooled well.
[0025] Furthermore, when pressure is released from the solid heat medium 5, the lubricating action of the grease (base oil component) allows the entire RbMnFe complex powder to smoothly return (expand or shrink) to the state before pressure was applied. In addition, by filling and reducing the gaps between the RbMnFe complex powders with resin powder, when pressure is released from the solid heat medium 5, the entire RbMnFe complex powder can be smoothly returned to the state before pressure was applied, in conjunction with the action of the grease. As a result, the amount of heat absorption obtained by releasing pressure from the solid heat medium 5 can be well secured. Furthermore, by adopting a resin powder having a low thermal conductivity such as polypropylene powder, the resin powder can function as a heat insulating material for the solid heat medium 5. This makes it possible to suppress the heat from the solid heat medium 5 from being released before being transferred to the heating target, or the heat being released simultaneously with the heat absorption by the solid heat medium 5, making it impossible to lower the temperature of the cooling target.
[0026] The grease added to the solid heat medium 5 is a silicon-based grease containing silicon oil as a base oil and silica powder as a thickener. This ensures good fluidity of the powder of the RbMnFe complex when pressure is applied and released, and makes it possible to maintain the solid heat medium 5 in a solid state (compressed powder state) even if pressure is repeatedly applied to and released from the solid heat medium 5. However, the solid heat medium 5 may be one to which paraffin-based oil as a base oil and paraffin-based grease containing bentonite as a thickener are added instead of the silicon-based grease. That is, according to experiments by the present inventors, it has been confirmed that the solid heat medium 5 to which paraffin-based grease is added also exhibits heat absorption and dissipation performance equivalent to that of the solid heat medium 5 to which silicon-based grease is added.
[0027] Furthermore, the solid heat medium 5 may be one to which molybdenum disulfide-based grease containing an extreme pressure additive has been added. That is, according to experiments conducted by the present inventors, it has been confirmed that the solid heat medium 5 containing grease containing an extreme pressure additive also exhibits the same heat absorption and release performance as the solid heat medium 5 to which silicon-based grease or paraffin-based grease has been added, and can ensure good fluidity of the RbMnFe complex powder even when pressure is repeatedly applied and released to the solid heat medium 5.
[0028] In addition, in this embodiment, the amount of grease added to the solid heat medium 5 is 6% by weight, but is not limited to this. That is, according to experiments etc. conducted by the present inventors, it has been found that by adding the amount of grease to the solid heat medium 5 of 5% by weight or more and 10% by weight or less, preferably 6% by weight or more and 10% by weight or less, it is possible to ensure a sufficient amount of RbMnFe complex in the solid heat medium 5 and to effectively prevent the solid heat medium 5 from being unable to be maintained in a solid state (compressed powder state) due to an excessive increase in the fluidity of the powder of the RbMnFe complex.
[0029] Furthermore, in addition to the grease, polypropylene powder is added to the solid heat medium 5. This effectively reduces the gaps between the powder particles of the RbMnFe complex, and further improves the heat insulating properties of the solid heat medium 5. However, the solid heat medium 5 may contain, instead of the polypropylene powder, a resin powder (e.g., polytetrafluoroethylene powder) that can be broken down to a particle size similar to that of the RbMnFe complex.
[0030] Considering the characteristics of polypropylene powder and polytetrafluoroethylene powder, the resin powder added to the solid heat transfer medium 5 is preferably one having a compressive yield stress of 55 MPa or less. This makes it possible to fill the gaps between the RbMnFe complex powder particles when the RbMnFe complex powder is solidified, and to stably retain the resin powder in the gaps. However, the resin powder may be any material having a compressive yield stress of 55 MPa or more as long as it is deformed by the pressure applied to cause the RbMnFe complex to undergo a phase transition.
[0031] Furthermore, in consideration of the characteristics of polypropylene powder and polytetrafluoroethylene powder, the resin powder added to the solid heat transfer medium 5 should have a particle size of 20 μm or less, more preferably 5 μm or less. This makes it possible for the resin powder mixed into the RbMnFe complex powder or the resin powder crushed by pressure to satisfactorily fill the gaps between the RbMnFe complex powder particles. However, the resin powder may have a fine particle size comparable to the particle size of the RbMnFe complex, and is not necessarily limited to a particle size of 5 μm or 20 μm or less.
[0032] In addition, in consideration of the characteristics of polypropylene powder and polytetrafluoroethylene powder, it is preferable that the resin powder added to the solid heat transfer medium 5 has a thermal conductivity of 0.25 W / m·K or less. This makes it possible to further improve the heat insulation of the solid heat transfer medium 5. However, the resin powder may have a relatively low thermal conductivity, and is not necessarily limited to one having a thermal conductivity of 0.25 W / m·K or less.
[0033] Furthermore, the solid heat transfer medium 5 contains a RbMnFe complex as a phase transition material. This allows the phase transition temperature T LH The phase transition temperature T from the high-temperature phase to the low-temperature phase is lower than HLSince the pressure applied to the solid heat medium 5 becomes high, the RbMnFe complex can undergo phase transition from a high-temperature phase to a low-temperature phase, and heat can be released from the solid heat medium 5, without significantly lowering the temperature of the solid heat medium 5. In addition, by releasing the pressure applied to the solid heat medium 5, the RbMnFe complex can undergo phase transition from a low-temperature phase to a high-temperature phase, and heat can be absorbed by the solid heat medium 5, without significantly increasing the temperature of the solid heat medium 5.
[0034] However, the phase transition material forming the solid heat transfer medium 5 is not limited to the RbMnFe complex, and may be TiNi, BaTiO3, PbZr 0.95 Ti 0.05 The solid heat medium 5 may be an alloy containing Ti (elastic heat medium) such as O3, or an organic resin containing hydrogen bonds (pressure heat medium) such as neopentyl glycol (NPG), pentaerythritol (PE), or pentaglycerin (PE). Furthermore, the phase transition material forming the solid heat medium 5 may be Gd5Si2Ge2, La(Fe,Co,Si) 13 , MnCoGeB 0.02 The material may be an elastic calorific material such as PVDF-TrFE, Cu2ZnAl, or FeRh, or a pressure calorific material such as (NH4)SO4, AgI, rubber, AMP, TRIS, MNP, or NMP.
[0035] The solid heat medium of the present disclosure may be one to which only grease is added. FIG. 7 shows the evaluation results of the amount of heat dissipation obtained by applying pressure to a solid heat medium 5′ to which only grease is added. The solid heat medium 5′ is formed into a substantially cylindrical shape by pressurizing and solidifying a mixture of RbMnFe complex powder and silicon-based grease inside a mold, and the amount of grease added to the solid heat medium 5′ is 6% by weight. FIG. 7 shows the temperature change at the center of the solid heat medium 5′ (the center of the central cross section in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5′ for a predetermined time (for example, about 30 seconds) by the above-mentioned test device in an environment where the room temperature is about 20°C. The maximum temperature increase when a pressure of 500 MPa is applied to the solid heat medium 5′ was 33°C. From these evaluation results, it can be understood that the solid heat medium 5′ can be used for the heat absorption and dissipation system 1 and can heat the heating target well.
[0036] FIG. 8 shows the evaluation results of the amount of heat absorption obtained by applying pressure to the solid heat medium 5' to which only grease is added, and then releasing the pressure from the solid heat medium 5'. FIG. 8 shows the temperature change at the center of the solid heat medium 5' (the center of the cross section at the center in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5' for a predetermined time by the above-mentioned test device in an environment where the room temperature is about 20°C, and then the pressure is released from the solid heat medium 5'. The maximum temperature drop when a pressure of 500 MPa is applied to the solid heat medium 5' and then the pressure is released is 30°C. From these evaluation results, it can be understood that if the solid heat medium 5' is applied to the heat absorption and dissipation system 1, the cooling target can be cooled well.
[0037] That is, even in the solid heat medium 5', the lubricating action of the base oil component of the grease ensures good fluidity at the micro level of the powder of the RbMnFe complex when pressure is applied and released, and the action of the thickening component of the grease makes it possible to maintain the solid state (compressed powder state) of the solid heat medium 5' even when pressure is repeatedly applied and released. As a result, it becomes possible to reduce the gaps between the powder particles of the RbMnFe complex when pressure is applied to the solid heat medium 5', and the entire powder of the RbMnFe complex can be pressurized almost evenly, thereby ensuring a good amount of heat dissipation obtained by applying pressure to the solid heat medium 5'. Furthermore, when pressure is released from the solid heat medium 5', the lubricating action of the grease makes it possible to smoothly return (expand or shrink) the entire powder of the RbMnFe complex to the state before pressure was applied, so that the amount of heat absorption obtained by releasing pressure from the solid heat medium 5' can be ensured. In addition, by adding grease to the solid heat medium 5', it is also possible to suppress adhesion between the solid heat medium 5' and the pressurizing member 4 that applies pressure to the solid heat medium 5'.
[0038] The present disclosure is not limited to the above embodiment, and various modifications can be made within the scope of the present disclosure. Furthermore, the above embodiment is merely a specific form of the invention described in the Summary of the Invention, and does not limit the elements of the invention described in the Summary of the Invention. [Industrial Applicability]
[0039] The present disclosure is applicable to the solid heat transfer medium manufacturing industry and the like. [Explanation of symbols]
[0040] 1 heat absorption and dissipation system, 4 pressure member, 5,5' solid heat medium.
Claims
1. A solid heat transfer medium obtained by solidifying a powder of a phase-transition material that undergoes a phase transition from a high-temperature phase to a low-temperature phase in response to application of pressure and that undergoes a phase transition from the low-temperature phase to the high-temperature phase in response to release of pressure, A solid heat transfer medium containing, as an additive, grease containing at least a base oil component and a thickening component.
2. The solid heat transfer medium according to claim 1, The grease is a solid heat transfer medium which is a silicon-based grease containing silicon oil as a base oil and silica powder as a thickener, or a paraffin-based grease containing paraffin oil as a base oil and bentonite as a thickener.
3. 3. The solid heat transfer medium according to claim 1, further comprising a resin powder as the additive in addition to the grease.
4. The solid heat transfer medium according to claim 3, The resin powder is a solid heat transfer medium having a particle size that allows the voids between the powder particles to be filled when the powder of the phase change material is solidified.
Citation Information
Patent Citations
Heat absorption / release system
WO2023002698A1